ANALISIS PERLAKUAN AKUNTANSI AGRIKULTUR PADA PETANI KELAPA PADA DESA DI DAERAH LIKUPANG SELATAN : DAMPAK RENCANA PENERAPAN ED PSAK NO.69 TENTANG AGRIKULTUR - Korompis, Claudia W.M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Biological assets is a unique asset, because of the transforming growth even after biological assets generate an output. Although it has many unique, but the financial management of biological assets still have to refer to the Financial Accounting Standards. Currently the Financial Accounting Standards Board (DSAK) issued SFAS No. ED 69 on agriculture which will come into force on 1 January 2017. According to this SFAS Biological assets are measured at initial recognition and at the end of each reporting period at fair value less costs to sell. Many of Regions, especially in the village do not know the accounting treatment for biological assets. This makes researchers want to analyze the impact of the application of IAS 69 ED is the continuation of agricultural farmers' efforts in this regard coconut trees in the village in the district South Likupang. With the proper financial management from the village, will support the country's economy as a whole, especially in the face of the MEA. This research uses descriptive analysis. The results of this study indicate that in general the village in the Regional South Likupang not apply to recognize the fair value of their assets. The traditional system by recognizing the asset at the acquisition price is still the basis in preparing the financial statements. But with this study are expected, farmers / entrepreneurs start applying SFAS palm plant began in 2017. Keywords: Accounting, Agriculture, ED IAS 69, Village.